PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM MINORITAS (SUBYEK HUKUM ASING) PT. PERSERO BANK BNI - Marianus Yohanes Gaharpung (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 1999)
Penjualan saham Bank BNI melalui bursa saham dalam negeri menimbulkan masalah yaitu munculnya subyek hukum asing dalam aspek pengaturan perusahaan. Atau dengan kata lain sejauh mana keterlibatan pemegang saham minoritas di dalam Perseroan Bank BNI. Salah satu segi yang cukup menonjol dalam UU Perseroan Terbatas No. l Tahun l995 adalah perlindungan saham minoritas.The selling shares of Bank BNI through domestic stock exchange emerger problem that is the emerging of forergin law subject in company regulation aspect. In other word, to what extent the involvement of the minority of shareholders in limited Company of Bank BNI. One of aspects which is obvious enough in law number 1 of the year 1995 on limited liability company is a protection for the minority of share holders.